Food environment in the Philippines: Issues, priorities and needs. Collaborative Needs Assessment Workshop Report - Bioversity International; World Vegetable Center; Department of Science and Technology – Food and Nutrition Research Institute (DOST-FNRI); International Institute of Rural Reconstruction (IIRR) (CGIAR, 2023)
The CGIAR Initiative on Fruit and Vegetables for Sustainable Healthy Diets (FRESH) aims to use an end-to-end approach to increase fruit and vegetable intake and in turn improve diet quality, nutrition, and health, while also improving livelihoods, empowering women and youth, and mitigating environmental impacts. This report presents key insights from a collaborative needs assessment (CNA) workshop conducted under Work Package 5 on Food Environments, which seeks to cultivate environments that encourage healthy and nutritious food choices. The CNA workshop was jointly organized by the Alliance of Bioversity International and CIAT, the World Vegetable Center, the International Institute of Rural Reconstruction, and the Department of Science and Technology–Food and Nutrition Research Institute. It brought together 38 stakeholders representing government, civil society, academia, research institutions, and the food production sector to identify needs, priorities, and gaps between consumer perspectives and stakeholder perceptions. Discussions shed light on the social, economic, and environmental factors that shape access to and consumption of fruits and vegetables in the Philippines, offering a foundation for developing strategies that foster healthier, more sustainable diets.